Kualitas Pelayanan Badan Penyelenggara Jaminan Sosial Kesehatan Perspektif Undang-Undang Nomor 24 Tahun 2011 (Studi Di Kota Madiun) - Sarjiyati; Bambang Sukarjono; Yuni Purwati; Yuan Salsabilla Rosada (Universitas Merdeka Madiun, 2022)
Abstract–This study aims to determine the quality of health services obtained by users of the Social Security Administering Body according to the perspective of Law Number 24 of 2011 and the efforts that must be made to improve the quality of these services. This study uses a type of empirical juridical research that is based on normative law, but observes how the interaction occurs when the norm works in society. With this research, it is expected to be one of the considerations for the government in making regulations to improve the quality of health insurance in Indonesia as well as, as a reference in improving the quality of services, especially by the Madiun City Health Social Security Organizing Agency.